Financing rural development for a harmonious society in China : recent reforms in public finance and their prospects - Fock, Achim (Policy research working paper, 2008)
"The Government of China has placed strong emphasis on addressing problems related to agriculture, farmers, and rural society, with the development of a "new socialist countryside" designated as a top priority for the Eleventh Five-Year Plan (2006-2010). The financing of public services in rural areas will be a key determinant of the Plan's success. This report analyzes the performance of the intergovernmental fiscal system - the financing of rural development through counties, townships, and villages - and the impact of recent reforms. The authors show that achieving the government's objectives will require channeling substantial new resources to rural areas. In addition, ensuring the effective transfer of resources and their efficient utilization will require fundamental reforms to a wide range of public institutions, including budget and planning processes, personnel management systems, and the organization of government agencies. The authors argue that a comprehensive reform strategy is needed to address fundamental vertical and horizontal imbalances in the intergovernmental fiscal system The reforms must reach beyond the fiscal system to build improved accountability mechanisms to improve public service delivery at the grassroots level. And, given China's size and diversity, reform efforts must focus on improving incentive structures at the county, township, and village levels. "--World Bank web site